Development of Antimicrobial Stapled Peptides Based on Magainin 2 Sequence - Hirano, Motoharu; Saito, Chihiro; Yokoo, Hidetomo; Goto, Chihiro; Kawano, Ryuji; Misawa, Takashi; Demizu, Yosuke (Molecules (Basel, Switzerland), 2021)
Magainin 2 (Mag2), which was isolated from the skin of the African clawed frog, is a representative antimicrobial peptide (AMP) that exerts antimicrobial activity via microbial membrane disruption. It has been reported that the helicity and amphipathicity of Mag2 play important roles in its antimicrobial activity. We investigated and recently reported that 17 amino acid residues of Mag2 are required for its antimicrobial activity, and accordingly developed antimicrobial foldamers containing α,α-disubstituted amino acid residues. In this study, we further designed and synthesized a set of Mag2 derivatives bearing the hydrocarbon stapling side chain for helix stabilization. The preferred secondary structures, antimicrobial activities, and cell-membrane disruption activities of the synthesized peptides were evaluated. Our analyses revealed that hydrocarbon stapling strongly stabilized the helical structure of the peptides and enhanced their antimicrobial activity. Moreover, peptide 2 stapling between the first and fifth position from the N-terminus showed higher antimicrobial activity than that of Mag2 against both gram-positive and gram-negative bacteria without exerting significant hemolytic activity. To investigate the modes of action of tested peptides 2 and 8 in antimicrobial and hemolytic activity, electrophysiological measurements were performed.